What do Scientific Publications Say about Inclusion in Environmental Education: A Bibliometric Analysis (2014-2024) (Papeles, 2026)
Introduction: Environmental education is a necessity; however, it has not been designed to contribute to all contexts and realities, as it is not structured from an inclusive perspective. Therefore, the objective was to conduct a bibliometric review, using the Biblioshiny tool, to analyze the scientific output on inclusion in environmental education during the period between 2014 and 2024. Methodology: The study employs a quantitative approach with a descriptive documentary design, using Scopus as the primary database due to its coverage and overall quality. The search, conducted in December 2025, used standardized terms from the Unesco Thesaurus and followed the PRISMA protocol, resulting in a final sample of 242 documents after applying filters for language, publication date, and type. Data processing was performed using VOSviewer 1.6.20 and the bibliometrix package in R with its Biblioshiny interface. Results and discussion: The results demonstrate exponential growth in academic interest in the topic, establishing inclusive education as a unifying element. However, a fragmentation is perceived in its integration with environmental education, which tends to be approached from an ethical framework of social justice and equity rather than a traditional biological perspective. A high density of research related to childhood and disability was identified, while higher education and technologies show research gaps. Conclusions: Given that this is an emerging field, there is a critical need to equip teachers with cross-cutting pedagogical tools and to strengthen the visibility of vulnerable contexts.
Keywords: Inclusion; environmental education; disability; bibliometrics; scientific publishing